BASIC PRINCIPLES OF PROVIDING CONTINUOUS PROFESSIONAL DEVELOPMENT OF TEACHERS (Innovative professional education, 2024)
The article defines the most important aspects of the continuous professional development of pedagogical workers of the institution of professional preliminary higher education in the modern educational space. The need to develop modern approaches to professional development in accordance with current legislation is substantiated. The procedure for organizing and conducting professional development of pedagogical staff of an educational institution is described. The importance of continuous continuous development of a teacher throughout his life to ensure the quality of education regarding the training of a modern competitive specialist is determined.
Keywords: continuous professional development, professional growth, professional competences, professional development, certification of teaching staff, subjects of professional development, self-education, self-development